Does improving hematological iron status restore the menstrual cycle in female athletes? - Lagowska, K. (Science & Sports, 2018)
Objectives: The aim of this study was to assess whether a 12-week nonpharmalogical nutritional intervention NI aimed at improving iron status in female athletes can mitigate disorders in the menstrual cycle.